Efektivitas Rehabilitasi Avour Buntung dalam Pengendalian Limpasan Air Hujan dan Pasang Laut - Dyan Eka Nurhayati; Jenny Caroline (Universitas Muhammadiyah Surabaya, 2026)
Developing river geometry is one method that can be implemented to reduce flooding caused on by sea tides and surface run-off. The objectives of this study is to determine the riverbed slope factor and wet area in order to identify the optimum river geometry during flood discharge. When Q25 occurs at 167,35 m3/sec and sea tide elevation is +2,9 m, the current state of the Avour Buntung is unable to accomodate it considering the avour capacity is only 156,302 m3/sec. The initial 0,097% avour bed slope was divided into four sections with slopes of 0,023%, 0,46%, 0,018%, and 0,016%. The average width of the section with the lowest embankment will be 25,28 meters. The Avour Buntung can accommodate the discharge when the maximum condition of Q25 and sea tide occurs because the avour storage capacity develops to 185,228 m3/sec and the avour has an average barrier height of 0.89 m.